PENGEMBANGAN PENILAIAN HASIL BELAJAR FISIKA BERBASIS ONLINE PADA MATERI GERAK LURUS DENGAN MENGGUNAKAN APLIKASI KAHOOT - Salti, Oktavia Indri; Lolowang , Jimmy; Rampengan, Alfrie Musa (Charm Sains: Jurnal Pendidikan Fisika, 2023)
This study aims to develop an online-based assessment of physics learning outcomes on straight motion material and to find out the implementation and responses of students after using the kahoot application as a medium for evaluating learning outcomes. This research is research and development (Research and Development) using the 4D research model adapted from Thiagarajan namely Difine, Design, Develop, and Dessiminate. The research instrument used was a test instrument, material expert validation sheets, media expert validation sheets, item analysis and student response questionnaires. The results of the eligibility validation of small group material experts were 78%, large groups were 92%, small group media expert validations were 78%, large groups were 84% with feasible and very feasible criteria. The response of the students in the small group test was 75.87%, the large group test was 80.6% with interesting criteria. The results showed that the development of the assessment of physics learning outcomes using the kahoot application was well implemented and feasible to be used in the assessment of learning outcome.